Effect of growth regulators on betalain profile in callus culture of Celosia sp. Issue 1 (May 2021) - Mastuti, R; Munawarti, A; Siswanto, D
Abstract: Red and yellow inflorescence of Celosia indicated the content of betalain pigment, betacyanin and betaxantin. In vitro system through callus culture is one of the strategies for producing plant bioactive compounds including betalain. Therefore, this study aims to analyse the content and profile of betalain pigments in Celosia callus in vitro induced by a combination of auxin and cytokinin. Callus was induced from in vitro cotyledonary and hypocotyl sprouts at 1 week after germination. Callus induction medium was MS + BAP + 2, 4-D or NAA. Subsequently, the profile and content of betalain pigments in each type of pigmented callus and in vitro hypocotyl and leaves were analysed by HPLC method. Repeated subcultures every two weeks resulted three types of pigmented callus: red, yellow and greenish white. HPLC analysis of in vitro hypocotyl, leaf and callus tissue derived from red and yellow Celosia inflorescence detected six types of compounds, namely 1) amaranthin, 2) isoamaranthin, 3) betalamic acid, 4) miraxanthin V, 5) 3-methoxytyramine betaxanthine and 6) (S)-tryptophan betaxanthine. Callus from red Celosia contains a small amount of betaxanthin which was higher in yellow Celosia . BAP:2, 4-D combination produced higher total content of betalain pigments.